The Implementation of Character Education on the Thematics Learning for the Fourth Graders of Primary Schools - Sofiasyari, Irma; Atmaja, Hamdan Tri; Suhandini, Purwadi (JESS (Journal of Educational Social Studies), 2020)
This research aims to describe the character education implementation in the fourth-grade thematics learning of primary schools. This research applies a descriptive qualitative method. The technique of collecting the data is purposive sampling. The subjects consisted of SD Islam Al Madina, SDN Petompon 01, and SD Marsudirini. The techniques for collecting the data were deep interviews, observation, and documentation. The techniques of the data validity were a source and method triangulation. The findings showed the character education on thematic learning of the fourth graders of the schools had been promoted by integrating the character values in three stages. They were planning, acting, and evaluating. Each stage had different activities and internalized different character values. They were adjusted with the specific features, vision, mission, and objectives of the schools. The implications of this research are to describe the ways to implement character education in thematic learning at Primary Schools. Thus, the character values could be internalized well for the students during the classroom learning activity.